Growth defect of domain III glycoprotein B mutants of human cytomegalovirus reverted by compensatory mutations co-localizing in post-fusion conformation - Mollik, Madlen; Rohorzka, Andreas; CHEN, XIAOHAN; Kropff, Barbara; Eisler, Lukas; Külekci, Büsra; Puchhammer-Stöckl, Elisabeth; Thomas, Marco; Görzer, Irene (mBio, 2024)
Cell entry is a crucial step for a virus to infect a host cell. Human cytomegalovirus utilizes glycoprotein B (gB) to fuse the viral and host cell membranes upon receptor binding of gH/gL-containing complexes. Fusion is mediated by major conformational changes of gB from a metastable pre-fusion to a stable post-fusion state whereby the central trimeric coiled-coils, formed by domain (Dom)III α helices, remain structurally nearly unchanged. To better understand the role of the stable core, we individually introduced three potentially helix-breaking or one disulfide bond-breaking mutation in the DIII α3 to study different aspects of the viral behavior upon long-term culturing. Two of the three helix-breaking mutations, gB_Y494P and gB_I495P, were lethal for the virus in either fibroblasts or epithelial cells. The third substitution, gB_G493P, on the other hand, displayed a delayed replication and spread, which was more pronounced in epithelial cells, hinting at an impaired fusion. Interestingly, the disulfide bond-breaker mutation, gB_C507S, performed strikingly differently in the two cell types - lethal in epithelial cells and an atypical phenotype in fibroblasts, respectively. Replication curve analyses paired with the infection efficiency, the spread morphology, and the cell–cell fusogenicity suggest a dysregulated fusion process, which could be reverted by second-site mutations mapping predominantly to gB DomV. Our findings underline the functional importance of a stable DomIII core for a well-regulated DomV rearrangement during fusion.
CRIS-Team Scopus Importer:2024-11-08
Keywords: entry and spread; glycoprotein B; glycoprotein O; human cytomegalovirus; membrane fusion